Mechanisms for international cooperation in research and development: Lessons for the context of climate change - Carlos María Correa (South Centre, 2012)
This Research Paper examines possible modalities of collaboration for research and development (R&D), understood as comprehensive of scientific studies and of activities for the generation of new processes and products and the improvement of existing ones . It briefly discusses, first, the various sources of technology for adaptation to and mitigation of climate change. Second, the paper examines different elements relevant for fostering cooperation in R&D and the modalities that such cooperation may adopt, having in view experiences made in other areas of science and technology. Finally, an analysis of the cooperative model used to promote the development and diffusion of seeds in the 'green revolution' is presented, with the aim of exploring its possible applicability to the case of environmentally sound technologies.
Keywords: 300